The Impact of Drinking Water Fluoride on the Risk of Hypothyroidism Development: A Review of the Latest Research - Stencel, Nicola; Szczot, Jakub; Krupa, Konrad; Skulimowska, Karolina; Trela, Katarzyna; Tuteja, Aleksander; Więcko, Laura; Olczyk, Liwia; Burzykowska, Klaudia; Gęborys, Kamila (Quality in Sport, 2026)
Introduction and purpose: Thyroid diseases are common endocrine disorders, with hypothyroidism being the most frequently diagnosed condition of the gland. Water fluoridation is an effective strategy for preventing dental caries, as confirmed by epidemiological studies. Despite the reported benefits, there are concerns about the risk of thyroid dysfunction with high fluoride exposure. The aim of this paper is to review the latest research on the impact of fluoride in drinking water on the risk of developing hypothyroidism. Materials and methods: A literature search was conducted using the medical databases PubMed and Google Scholar. Articles were retrieved in English, employing the keywords: “hipothyroidism”, “thyroid function”, “water fluoridation”, “fluoride”, “iodine”. State of Knowledge: Hypothyroidism affects approximately 4% of Europeans, with an annual incidence of 226 cases per 100,000 people. Drinking water is the main source of chronic fluoride exposure, and over 500 million people live in areas of endemic fluorosis. Numerous studies indicate a clear correlation between fluoride concentration in water and TSH levels, suggesting that excessive fluoride exposure increases the risk of hypothyroidism, which can have serious health implications, especially for pregnant women. Summary: Recent studies confirm the correlation between fluoride exposure and the development of hypothyroidism, emphasizing the need to monitor the impact of fluoride on health.